Evaluation of Central Java Tarung Derajat Athlete Development at Nationals - Meiliyana Citra Kurnia Wardhani; Roas Irsyada (Journal of Physical Education Health and Sport, 2026)
Sports performance development plays a strategic role in improving athlete performance and national competitiveness. In competitive sports, athlete success is determined not only by individual ability but also by the effectiveness of a structured, tiered, and sustainable development system. Tarung Derajat, a traditional Indonesian martial art that has developed into a competitive sport, requires systematic evaluation to ensure continuous improvement, particularly at the provincial level. Central Java is one of the provinces that consistently contributes to the Tarung Derajat national championship. This study aims to evaluate the progress of the development of Central Java Tarung Derajat athletes in the results of the National Championship. The research method used was the evaluation of the CIPP (Context, Input, Process, Product). This research is a qualitative descriptive research with a survey method. The respondents in this study were administrators, coaches, and athletes from Central Java. Data collection techniques through observation, interviews and open questionnaires as well as documentation. The stages of analysis include data reduction, data presentation, and drawing conclusions or verification. The results of the study show that in the aspect of  context, the coaching has a clear vision and mission;  input, certified coaches, athletes who have motivation to achieve, and adequate facilities and infrastructure, although funding from National Sports Committee of Indonesia (KONI) is still limited;  process, training programs have been prepared in a planned manner through micro and macro programs and monitoring and evaluation are carried out; product, the athlete's achievement has reached the minimum target set. However, limited funding, athlete training time, and uneven nursery systems are factors that hinder more significant achievements, especially towards the international level. Therefore, the progress of coaching athletes in Central Java is categorized quite well and still needs to strengthen the continuous coaching program.